Effects of Magnesium Content on Structure and Electrochemical Properties of La-Mg-Pr-Al-Mn-Co-Ni Hydrogen Storage Alloys - L. M. C. Zarpelon; E. P. Banczek; L. G. Martinez; N. B. Lima; I. Costa; R. N. Faria (Advances in Materials Science and Engineering)
The discharge capacity, microstructures, and corrosion resistance of some as-cast alloys represented by the formula La0.7−xMgxPr0.3Al0.3Mn0.4Co0.5Ni3.8, where x = 0.0, 0.1, 0.3, 0.5, and 0.7, were investigated by SEM/EDX, XRD, and electrochemical measurements. The partial substitution of La by Mg refined the grain structure while the total substitution changed it from equiaxed to columnar. Three phases were detected: a major phase (M), a grey phase (G), and a dark phase (D). The compositions analyzed by EDX suggested that the M phase was close to a LaNi5 phase. With the increase of the Mg content, the analyses revealed a G phase with composition close to a RMg2Ni9 (R = La,Pr) and a D phase close to a MgNi2 phase. The XRD analysis and Rietveld refinement corroborated the EDX results. The corrosion resistance of the alloys was evaluated in 6.0 mol·L−1 KOH solution, and the results showed that the substitution of La by Mg was beneficial for this alloy property. Nevertheless, Mg addition was deleterious to the discharge capacity of the electrodes.